Hubungan Kadar Timah Hitam dalam Darah dengan Jumlah Lekosit, Trombosit, dan Aktifitas Superoxide Dismutase (SOD) pada Pekerja Timah Hitam di Kabupaten Tegal - Lily Gunawan; Onny Setiani; Suhartono Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Bacground: Air pollution is a serious matter which can damage environments also human health. In Indonesia,Lead (Pb) has huge potential to harm and to damage environments on industrial area. The inserted of lead intohuman bodies especially by inhaling of lead´s dust through respiratory tract, most of the Lead will bounded in redblood cells, than the rest of it will be accumalated in bone marrow and soft tissues and would bring impact ofdisturbances of haematopoesis, cardiovascular, renal, nervous, gastrointestinal, and reproductive systems andalso carcinogenic. This study aimed to find out the degree of exposure to Lead and its effect haematologic systemmainly leukocyte count, platelet count and activity of Superoxide Dismutase (SOD).Methods: It was an observational research using cross sectional design. The subject of research was 41 workers.Blod Lead Level (BLL)l as independent variable was examined using AAS. Dependen variable of this research wasblood profile consist of Lekosit, Trombosit, dan Activity of Superoxide Dismutase (SOD). Data would be analyzedusing Kendall Tau correlation.Result: Blood lead level (BLL) wasmeasured using AAS examination of 41 workers found on average 27.069 μg/dl, Permmision Exposure Limit 0.6 μg/dl – 108.3 μg/dl exceed the limit of Centre for Disease Controle andPrevention (CDC=10 μg/dl). Examination of leukocyte count results p 0.034 (p<0.05), average 7256,9/mm³,range 3800–12700/mm³, while platelet count p 0.857 (p>0.05), average 277634.2/mm³, range 143000–391000/mm³, and SOD activity p 0.220 (p>0.05), average 82.304 U/ml, range 72.11-95.92 U/ml still normal.Conclusion: The level of BLL on workers had been over treshhold limit value (TLV)and It had significantlycorrelation with the level of leucocite (p-value < 0.05)Recommendation: Medical and preventive action are needed to restore and prevented worsening effect on healthby administering medication, routin check-up, natural chelating agent and supplement and healthly environmentprograms applied.Key words: Blood Lead Level (BLL), leukocyte count, platelet count, Superoxide Dismutase (SOD) activity.